Dioxins - Montoya, Nelson (Revista Universidad de Guayaquil, 2008)
Dioxins are a group of chemical substances. They are all characterized as colorless, odorless, polychlorinated aromatic compounds with similar chemical and physical structures and properties. These compounds are not intentionally or deliberately produced by man, but are formed as waste products in different chemical processes. Dioxins are naturally present in volcanic eruptions and forest fires, but their origin of greatest concern corresponds to their formation within anthropogenic processes such as urban waste incineration, paper manufacturing, herbicides and defoliants, high-temperature metal production, PVC manufacturing, etc. Although formally Dioxins is the name applied to a group of 210 polychlorinated organic compounds-polychlorinated dibenzodioxins (PCDD’s) and polychlorinated dibenzofurans (PCDF’s)-, of this group only 17 compounds are of toxicological interest and concern. The 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin, abbreviated as 2, 3, 7, 8-TCDD is the most studied of these compounds, due to its higher toxicity and carcinogenicity recognized by the World Health Organization (WHO). It is determined in parts per trillion. This group also includes certain compounds of the family of polychlorinated biphenyls (PCBs), which are included on the basis of the similarity of properties of these compounds with dioxins, hence their name “dioxin-like PCBs”.